Pendampingan Manajemen Bandwidth Jaringan Komputer menggunakan Mikbotam pada SMKN 1 Lingsar - Andi Sofyan Anas; Hasbullah Hasbullah; Ahmad Zuli Amrullah; Ria Rismayati; Muhammad Innuddin; Rifqi Hammad (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2021)
Internet is one of the most important needs in human life. The need for the internet is increasingly crowded, making the world of education in Indonesia very enthusiastic about using it as a means of learning and learning. The use of the internet as a learning and learning tool makes it easier for educators (teachers) to interact with students (students) regardless of their position or distance. However, in meeting the need for a stable and fast internet, it is necessary to provide assistance on bandwidth management. In this assistance, one must be able to understand how much bandwidth is capable of optimizing internet connections for the learning and learning process at SMKN 1 Lingsar. In addition to these needs, it is important to know that bandwidth utilization is shared everywhere so that internet optimization for learning goes well. Therefore, optimal assistance aims to enable users to perform bandwidth management according to the stages of using mikbotam, so that monitoring of bandwidth usage can be carried out more optimally by SMKN 1 Lingsar. The mentoring method is carried out in 5 stages, namely planning, preparation, implementation, evaluation, and reporting. The results obtained from this service program are participants are able to perform bandwidth management according to the stages that have been given.